2013
DOI: 10.4103/0253-7176.116244
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Attitude towards Mental Illness in an Urban Community in South Delhi - A Community Based Study

Abstract: Background:Mental illness have been largely ignored or neglected because of a community's perception and attached social stigma.Materials and Methods:A community based cross-sectional study was conducted in an urban community in South Delhi to study perception and attitude of the community about towards mental illness. An adult member in household selected by systematic random sampling was interviewed using semi-structured interview schedule for perception about mental illness and 34 item Opinion about Mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 13 publications
7
39
2
1
Order By: Relevance
“…The inheritance or genetic cause was not reported to be a reason for depression, but for psychosis over one third endorsed genetic cause, which is consistent with the findings from Bourget et al 15 , Matthias C et al 19 and Jorm et al 9 This can be explained that depression may be considered by the students as an commonest expected mental disorder which occurs in all communities because of routine life activities. Additionally, the present study findings were contradictory to the findings of Yoshibumi Nakane et al 12 and Harshal Salve et al 25 that evil spirits, virus or infection and allergy can be the causative factors. The present study shows even though the overall awareness of the students about the risk factors for developing depression and psychosis was low means that understanding of the students about the risk factors for psychosis was apparently poorer than for depression.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The inheritance or genetic cause was not reported to be a reason for depression, but for psychosis over one third endorsed genetic cause, which is consistent with the findings from Bourget et al 15 , Matthias C et al 19 and Jorm et al 9 This can be explained that depression may be considered by the students as an commonest expected mental disorder which occurs in all communities because of routine life activities. Additionally, the present study findings were contradictory to the findings of Yoshibumi Nakane et al 12 and Harshal Salve et al 25 that evil spirits, virus or infection and allergy can be the causative factors. The present study shows even though the overall awareness of the students about the risk factors for developing depression and psychosis was low means that understanding of the students about the risk factors for psychosis was apparently poorer than for depression.…”
Section: Discussioncontrasting
confidence: 99%
“…In present study most of the students have not identified witch-doctor or a priest to be helpful, which is consistent with previous findings from two studies 29,30 that turning to a practitioner of complementary medicine, and a priest was less frequently advised instead of informal self help from family and friends was endorsed. Present study has contradictory results from the studies 34,25 done in Delhi in which some laypeople preferred treatment from Tantric/Ojha for mental disorders. As reported by most of the previous mental health surveys 14,11,4,12,19 on young population, interpersonal interventions like giving the patient love and affection, listening and trying to understand the problems and making the patient more active physically were endorsed by the students as potentially helpful (80%), than pharmacological interventions for a patient.…”
Section: Discussioncontrasting
confidence: 65%
“…Similarly, a majority of students did not know that overly energetic behavior is a characteristic of bipolar disorder or that mental illness and mental retardation are not the same. Though this misconception and inconsistency can be explained by the lack of health literacy on mental health (Keyes, 2005;Jorm, 2000), remain serious because the ignorance could possibly be more in other groups of population (Salve et al, 2013). The students' responses to knowledge items also included some unexpected results.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, however, 90% of patients with mental disorders do not receive even basic mental health care [17]. Case-finding for them and their prognosis are often affected by the perception and attitude of society toward mental disorders, which is highly dependent on their knowledge toward mental disorders [18]. Cadres are expected to take a role not only to directly help patients, but also to indirect affect the above perception and attitude of individuals in community [18].…”
Section: Cadres' Perception Toward Mental Disorders and Internationalmentioning
confidence: 99%
“…Case-finding for them and their prognosis are often affected by the perception and attitude of society toward mental disorders, which is highly dependent on their knowledge toward mental disorders [18]. Cadres are expected to take a role not only to directly help patients, but also to indirect affect the above perception and attitude of individuals in community [18]. However, cadres have not shown their performance maximally for community mental health except some regions which experienced a terrible earthquake and tsunami [4].…”
Section: Cadres' Perception Toward Mental Disorders and Internationalmentioning
confidence: 99%